2021
DOI: 10.1007/s10637-021-01088-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1a/1b trial of CSF-1R inhibitor LY3022855 in combination with durvalumab or tremelimumab in patients with advanced solid tumors

Abstract: Background LY3022855 is a recombinant, immunoglobulin, human monoclonal antibody targeting the colony-stimulating factor-1 receptor. This phase 1 trial determined the safety, pharmacokinetics, and antitumor activity of LY3022855 in combination with durvalumab or tremelimumab in patients with advanced solid cancers who had received standard anti-cancer treatments. Methods In Part A (dose-escalation), patients received intravenous (IV) LY3022855 25/50/75/100 mg once weekly (QW) combined with durvalumab 750 mg on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Similar toxicities were seen for other anti-CSF-1R/PD-1 combination treatments. [29][30][31][32][33][34] ICBs are now standard treatment options with response rates to single agent PD-1/PD-L1 mAbs ranging from 10% to 30% across a number of solid malignancies including NSCLC, UBC and MEL [35][36][37][38][39][40][41] but can be increased to 60% when combined with CTLA4 blockade in MEL. However, this increased therapeutic benefit comes at the price of significantly increased toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar toxicities were seen for other anti-CSF-1R/PD-1 combination treatments. [29][30][31][32][33][34] ICBs are now standard treatment options with response rates to single agent PD-1/PD-L1 mAbs ranging from 10% to 30% across a number of solid malignancies including NSCLC, UBC and MEL [35][36][37][38][39][40][41] but can be increased to 60% when combined with CTLA4 blockade in MEL. However, this increased therapeutic benefit comes at the price of significantly increased toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Two phase I trials involving LY3022855 monotherapy (NCT02265536, NCT01346358) and one phase I trial involving AMG 820 (NCT01444404) in the management of advanced solid tumors reported zero objective responses (0/86 and 0/25, respectively), though decreases in TAMs were noted in addition to elevations in circulation CSF-1 levels, indicating that proper target engagement occurred [179][180][181]. When LY302285 is used in combination with ICIs including tremelimumab (anti-CTLA-4) or durvalumab (anti-PD-L1), ORR approaches 4.2% (3/72) [182]. Similarly, for AMG820, when combined with pembrolizumab (anti-PD-1) for advanced solid tumors, ORR has been documented at 2.6% (3/116), well below expected response rates seen with pembrolizumab monotherapy [183].…”
Section: Csf-1rmentioning
confidence: 99%
“…Among patients with diffuse type TGCT, instead, emactuzumab therapy resulted in improved and durable clinical responses, as well as in quality-of-life assessment [ 38 ]. LY3022855, a human immunoglobulin G subclass 1 (IgG1) anti-CSF1R mAb, has been tested alone (NCT01346358) or in combination with tremelimumab (NCT02718911) in patients with advanced solid tumors, demonstrating limited clinical activity despite a good safety profile [ 39 , 40 ].…”
Section: Targeting Immune System In Cancermentioning
confidence: 99%